[Postcolonial Economies] [By Jane Pollard, Cheryl McEwan and Alex Hughes, Eds, London and New York: Zed Book, 2011. ISBN 978-1848134041] - Profant, Tomáš Imrich, 1983-
Recenzia na publikáciu, ktorá sa zaoberá postkoloniálnym prístupom v ekonomike.